DESCRIPTIVE AND COMPARATIVE ANALYSIS OF THE EFFECT OF WEATHER/SEASONS ON PRODUCT SALES IN GROCERY STORES - Whydiantoro; Nindi Lestari (Universitas Majalengka, 2026)
Product sales in grocery stores are influenced by various factors, one of which is weather or seasonal conditions. Weather changes, such as the rainy season and the hot season, can influence consumer preferences when purchasing certain products. This study aims to analyze the effect of weather changes on sales patterns of two temperature-sensitive products: instant noodles and cold drinks. The method used was descriptive and comparative analysis based on eight weeks of weekly sales data, including heavy rain, light rain, and hot/scorching weather. The results showed that instant noodle sales increased significantly during the rainy season, with an average of 28.75 cartons per week, compared to only 13.5 cartons per week in the hot season. Conversely, cold drink sales increased sharply during the hot season, with an average of 28.25 cartons per week, compared to 11.5 cartons per week in the hot season. These findings confirm a direct relationship between weather conditions and consumer purchasing behavior and demonstrate the importance of adaptive inventory management strategies based on seasons so that grocery stores can minimize the risk of understocking or overstocking. This research also provides a basis for small business owners to make more informed and efficient procurement decisions.